Safe application of extensive radiotherapy to a cardiac resynchronization device. (11th October 2020) - Schernthaner, Christiana; Kopp, Michael; Dagn, Karin; Rettenbacher, Lukas; Weiss, Lukas; Meyersburg, Damian; Brandt, Mathias‐Christoph; Hoppe, Uta C.; Strohmer, Bernhard
Abstract: Patients with cardiac implantable electronic devices undergoing radiotherapy (RT) are prone to the risk of device failure. Guidelines and manufacturer's instructions are lacking practical recommendations for cumulative radiation doses to pacemakers or implantable cardioverter defibrillators. The present case demonstrates the effect of RT of a Merkel cell carcinoma near the location of a cardiac resynchronization therapy pacemaker. Despite guideline recommendations, surgical relocation or de novo implantation of the device on the contralateral side was avoided to prevent the dissemination of tumour cells, inflammation, and wound healing complications. A total dose of 47.25 Gy applied in very close proximity to the cardiac resynchronization therapy pacemaker was carried out safely without jeopardizing the patient and any device malfunction during and after treatment within >1.5 years of follow‐up period. The present case demonstrates that high‐dose RT near to a cardiac resynchronization therapy device can be carried out safely. Special precautions during RT as well as close device follow‐up interrogations are mandatory. Large‐scale studies are needed for the true frequency of adverse events.